RESULTS OF A PILOT CLINICAL TRIAL OF DENDRITICCELL BASED VACCINES FOR TREATMENT OF RECURRENT HERPESVIRUS INFECTION - O. Yu. Leplina; N. M. Starostina; D. D. Blinova; O. I. Zheltova; E. A. Oleinik; T. V. Tyrinova; A. A. Ostanin; E. R. Chernykh (Медицинская иммунология, 2016)
Chronic recurrent infections caused by herpes simplex virus (HSV) types 1 and 2 represent a serious medical and social challenge. Given an important role of immune system in surveillance of viral infections, an induced enhancement of antigen-specific immune response seems to be a promising approach to treatment of recurrent HSV infections, in particular, using dendritic cell (DCs) vaccines. The present paper contains results of an open pilot study evaluating efficacy and safety of dendritic-cell vaccines in the patients with recurrent HSV infections. Twenty-nine patients including 14 persons with labial herpes, and 15, with genital herpes have been enrolled in this study. DCs were generated in presence of GM-CSF and IFNα and then loaded with recombinant viral proteins (HSV1gD or HSV2gD). These cells were applied in 2 rounds of vaccination performed within 9 months. Immunotherapy with DCs did not induce sufficient side effects, and was accompanied by more than two-fold decrease in relapse rate and increased length of remissions during the 9-month period of treatment. Later on, we revealed a reduced frequency of relapses, and a 3-fold increase in remission duration over the subsequent 6-month follow up. The clinical effect during the treatment and at later terms (a half-year observation) was noted with both labial and genital herpes, as registered in the majority of patients, being associated with induction of antigen-specific proliferative response and normalization of reduced mitogenic responsiveness of mononuclear cells towards ConA. The patients’ survey at longer terms (more than 24 months) has shown that the beneficial effect of immunotherapy, in terms of reduced relapse rates, was maintained in 77.8% of the respondents by 48 months (a median follow-up term). At this time, the antigen specific proliferative response was maintained in 66.7% of patients. The data obtained suggest that the dendritic-cell vaccines may be a promising approach to the treatment of recurrent labial and genital herpes.